Students Interest in Research and Tendency to Acquire Research Skills among Postgraduate Students with Learning Disabilities (LD) in Two Public Universities of Cross River State, Nigeria: Implications for Psychology - Ikwen, Emmanuel Uminya; Denigwe, Chiaka Patience; Nwogwugwu, Chidirim Esther; Ovat, Sylvia Victor; Ntamu, Blessing Agbo; Ekpang, Pauline Unwada; Eteng, Matilda Ernest; Undiyaundeye, Florence A.; Eduwem, Joy Dianabasi; Uchegbu, Henriette Osayi; Dick, Roseline Ekim; Omoogun, Remi Modupe; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Learning disability is a permanent condition caused by abnormalities in the growth and development of the human brain, which has enormous implications for an individual's general performance. Aim: This study investigated how students’ interest in research predicted the tendency to acquire research skills among postgraduate students with Learning Disabilities (LD) in two Public Universities of Cross River State, Nigeria: Implications for Psychology. One objective, one purpose, and one statement of hypothesis were formulated. A literature review was carried out. Method: The survey research design was utilized. A stratified random sampling technique was adopted, and 49 respondents were sampled. A 16-item four-point modified Likert scale questionnaire was the instrument used for data collection. The face and content validity of the instrument were established. The reliability estimates are 0.84 using the Cronbach Alpha method. A simple linear regression statistical tool was used to test the hypothesis. The hypothesis was tested at the 0.05 level of significance. Results: The results revealed that interest significantly predicts postgraduate students with learning disabilities' tendency to acquire research skills. Hence, the more interested students with learning disabilities are in research, the more likely they are to develop strong research skills. Research skills are crucial for postgraduate studies, particularly for thesis writing, dissertation projects, and contributing to academic knowledge. By fostering research interest, universities can enhance the overall academic success of their postgraduate students. Conclusion: Interest in research significantly predicts postgraduate students' tendency to acquire research skills in the research area. Given the significant role of knowledge in humanity, acquiring research skills is integral to man. Graduate schools should have internal seminars and workshops, making it mandatory for students to present standard papers.